Structure service life assessment under combined loading using probability approach (Fracture and Structural Integrity, 2016)
This article presents a basic research approach for probabilistic assessment of vehicle structure fatigue endurance under multiaxial loading. One representative welded structural detail of the bottom joint plate of an articulated bus was selected for the case study. The character of the loading on the joint during a service test is analyzed and discussed. The methodology for estimation of the damage level in the joint builds on deterministic procedures for railway vehicle assessment based on shear, longitudinal and transverse stress components. This approach based on the equivalent stress and particular load capacity factors was expanded to include the probabilistic perspective. KEYWORDS. Service life; Combined loading; Damage; Vehicle; Probabilistic approach.
Keywords: Service life; Combined loading; Damage; Vehicle; Probabilistic approach